Faktor penentu prestasi pelajar Matrikulasi dalam subjek Perakaunan - Ishak, Zuaini; Abdul Manaf, Nor Aziah; Mat Zin, Rosliza (UUM College of Arts and Sciences, 2008)
This study explores the determinants of students’ performance in accounting at the matriculation level. Out of 450 questionnaires distributed, analysis on the 393 usable sample shows the overall average students’ grade point is at the range of C. Using stepwise multiple regression, the findings show significant positive relationships between the grade of management accounting subject with the previous cumulative grade point average and the achievement in financial accounting subject that was taken in the previous semester. Besides that, attitude, motivation and expected marks show significant relationships with the students’ performance. Interestingly, the results show that students without accounting exposure perform better than those with previous accounting exposure.